Information was key to efficient US-Anglo victory in Iraq. - Bowden, M. (IEEE spectrum)
Remote sensing, communications, and command gave the coalition forces a commanding advantage in the war in Iraq. Satellites were the most effective tool. The United States owns the ultimate in military high ground. Nearly 100 orbiting platforms provided secure communication links, navigational information, and detailed ground and atmospheric observation. Commanders on the ground received real-time images and targeting data from them on laptop computers. Remotely piloted aircraft also played a major role in the conflict.